Paradise lost Mahathir & the end of hope - Ignatius, Dennis J. (Dennis Ignatius, 2021)
Malaysiana LCMS is proud to distribute the bold new book by Dennis Ignatius (a former Malaysian ambassador) because he has courageously expressed publicly what many Malaysians only dare to say privately. Paradise Lost takes a critical look at Dr Mahathir Mohamad's role in Malaysia's political evolution and his ultimately destructive legacy of corruption, racism and religious extremism. He inherited a nation pregnant with promise and left it mired in division, uncertainty and instability, a grand kleptopia, a terrible kakistocracy. It also examines the role Mahathir played in Pakatan Harapan's stunning 2018 electoral victory and his subsequent betrayal of the coalition he was entrusted to lead. The end result is a nation in deep crisis, adrift in a sea of uncertainty, unable to come to terms with its past, unwilling to make the compromises necessary for its future. Paradise Lost makes for sober reading. Intensely provocative, it challenges long-established shibboleths, spotlights the dangers now confronting the nation and argues that Malaysia's only hope for redemption lies in embracing and harnessing its unique multicultural identity.